HOW INVERTEBRATES LIVE (Author: Kaye Mash) - Brennan, Michael (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1976)
Kaye Mash. HOW INVERTEBRATES LIVE. London: Elsevier Press. 1975. 160 pp. 11.95.